1999
DOI: 10.1046/j.1365-2362.1999.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological doses of calcium regulatory hormones do not normalize bone cells in uraemic rats

Abstract: The results show that administration of PTH and calcitriol in doses that raise serum calcium fails to normalize the percentage of osteoclast surface, but was effective in raising osteoblast number and osteoblast volume in experimental renal failure. The results argue for abnormal response of bone cells to calcium-regulating hormones and/or the action of factors other than calcium regulatory hormones in the genesis of skeletal abnormalities of renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Studies conducted to date using Nx combined with parathyroidectomy and PTH infusion [11,12] did not provide direct data of bone turnover. Moreover, the model of Szabo et al [13] manifested osteomalacia, a pathological condition different from ABD. Referring to these past studies, we tried various PTH infusion rates and diet compositions, and succeeded in developing a novel experimental model for studying ABD, using a PTH infusion rate of 0.1 mg/kg/h (the same as that used by Szabo et al [12]) with a diet containing 2% calcium and 1% phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted to date using Nx combined with parathyroidectomy and PTH infusion [11,12] did not provide direct data of bone turnover. Moreover, the model of Szabo et al [13] manifested osteomalacia, a pathological condition different from ABD. Referring to these past studies, we tried various PTH infusion rates and diet compositions, and succeeded in developing a novel experimental model for studying ABD, using a PTH infusion rate of 0.1 mg/kg/h (the same as that used by Szabo et al [12]) with a diet containing 2% calcium and 1% phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to address the role of dietary phosphorus and hyperphosphatemia in bone remodeling through histomorphometry. Szabó [20] performed an experimental study that evaluated whether physiologic doses of either PTH or calcitriol were able to normalize osteoclast and osteoblast function in uremic rats. The authors found that administration of PTH and calcitriol, in physiologic doses that raised calcium serum levels, failed to normalize the percentage of osteoclast surface.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, Szabo et al . [12] use a somewhat specialized experimental model evaluating the effect of a combination of very short‐term, mild uraemia and the aparathyroid state (PTX)—with development of hypocalcaemia prevented by a high‐calcium diet—on the histomorphometry of cancellous bone. As the authors state, this is only a pilot study in which the effects of uraemia and PTX cannot be discriminated.…”
mentioning
confidence: 99%
“…The pilot study of Szabo et al . [12], therefore, clearly focuses on the need for a much deeper understanding of the relationship between the known calciotropic hormones and bone cells in uraemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation